Pengaruh Pelarut Metanol dan Etanol Terhadap Kadar Flavonoid Total Ekstrak Kulit Pohon Waru (Hibiscus tiliaceus L.) - Astrid Kusuma Putri; Lunardhi Susanto; Deva Oktavy American Iswardjono; Asti Rahayu; Lindawati Setyaningrum (UNIVERSITAS MUHAMMADIYAH MATARAM, 2024)
Sea hibiscus (Hibiscus tiliaceus L.) is one of the plants in Indonesia that is empirically used as a traditional medicine. The study aims to determine the total flavonoid content of methanol and ethanol extracts from the sea hibiscus tree bark using UV-Vis spectrophotometry. Phytochemical screening of flavonoids is done using concentrated magnesium and hydrochloric acid (HCl). Total flavonoid levels are determined using the AlCl3 method specified in the QE (Quercetin equivalent). The phase of the research method includes preparation of methanol extract and ethanol extracts, phytochemical screening of flavonoid content, quantitative analysis of the flavonoid content (determination of the maximum wavelength (λmax) of quercetin, standard curve preparations of quercetin, and determination of flavonoid contents in methanol extract and ethanol extract), data management and analysis. Phytochemical screening showed methanol extracts and ethanol extract of the Sea Hibiscus tree bark showed positive contain flavonoids. Quantitative tests using UV-Vis spectrophotometry measured at 441 nm wavelengths showed that the concentration of flavonoid compounds in the Sea Hibiscus tree bark methanol extract was 0.109 %b/b, and the concentrations of flavonoids in the ethanol extracts were 0.096 %b/b.